Representing the Black female subject in western art - Nelson, Charmaine (Routledge, 2010)
Nelson analyzes not only how, where, why and by whom black female subjects have been represented in Western art, but also what the social and cultural impacts of the colonial legacy of racialized Western representation have been. She poses questions about the concepts of production, the consequences of comsumption and more
Disponible en ligne: https://doi-org.proxy.bibliotheques.uqam.ca/10.4324/9780203851241 Contenu: Through an-other's eyes : white Canadian artists – Black female subjects – Racing childhood : representations of black girls in Canadian art – Slavery, portraiture, and the colonial limits of Canadian art history – The fruits of resistance : reading portrait of a Negro slave on the sly – Tying the knot : Black female slave dress in Canada – Coloured nude : fetishization, disguise, dichotomy – The "hottentot venus" in Canada : modernism, censorship, and the racial limits of female sexuality – White marble, Black bodies, and the fear of the invisible Negro : – Signifying blackness in mid-nineteenth-century neoclassical sculpture – Vénus Africaine : race, beauty, and African-ness – Allegory, race, and the four continents : Jean-Baptiste Carpeaux's les quatre parties du monde soutenant la sphere céleste – Conclusion : whiteness as collective narcissism, towards a new vision.
Keywords: afro-féminisme; approches et analyses; arts; cours; discipline; féminisme afroaméricain; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; système colonial; systèmes d'oppressions; thématiques

Indigenous women and feminism: politics, activism, culture - Suzack, Cheryl; Huhndorf, Shari M.; Perreault, Jeanne; Barman, Jean (UBC Press, 2010)
"Can the specific concerns of Indigenous women be addressed within current mainstream feminist and post-colonial discussions? Indigenous Women and Feminism: Politics, Activism, Culture proposes that a dynamic new line of inquiry – Indigenous feminism – is necessary to truly engage with the crucial issues of cultural identity, nationalism, and decolonization particular to Indigenous contexts. Through the lenses of politics, activism, and culture, this wide-ranging collection examines the historical roles of Indigenous women, their intellectual and activist work, and the relevance of contemporary literature, art, and performance for an emerging Indigenous feminist project. The questions at the heart of these essays – What is at stake in conceptualizing Indigenous feminism? How does feminism relate to Indigenous claims to land and sovereignty? What lessons can we learn from the past? How do Indigenous women engage ongoing violence and social and political marginalization? – cross disciplinary, national, academic, and activist boundaries to explore in depth the unique political and social positions of Indigenous women."–Page 4 de la couverture."A vital and sophisticated discussion that will change the way we think about modern feminism, Indigenous Women and Feminism will be invaluable to scholars, activists, artists, community organizers, and those concerned with Indigenous and feminist issues at home and abroad."– Résumé de l'éditeur.
Le texte de Tsosie, Rebecca (2011). Native Women and Leadership: An Ethics of Culture and Relationship a été donné en lecture au cours POL4105.
Keywords: activisme; approches et analyses; arts; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; militance; pol4105; premier cycle; premières nations; système colonial; systèmes d'oppressions; territoire; thématiques; études autochtones; études féministes; études littéraires